Timing of glacial events in Antarctica - diamond drilling into the glaciomarine sequence of the Weddell Sea continental shelf - Koç, Nalân; Kuvaas, Berit; Kristoffersen, Yngve; Hansen, Erik; Persson, Allan (Report of the Norwegian Antarctic Research Expedition 1996/97, 1997)
Keywords: NARE 1996/97; Sørishavet; Weddellhavet; glasiologi; kontinentalsokkel; sedimenter; sedimentologi; seismologi

A model of ice shelf-ocean interaction with application to the Filchner-Ronne and Ross Ice Shelves - Nøst, Ole Anders; Foldvik, Arne (Journal of Geophysical Research: Oceans, 1994)
A simple analytical model has been developed to study the formation of Ice Shelf Water (ISW). ISW is assumed to flow as a buoyancy-driven layer underneath the ice shelf. A relation between potential temperature and salinity in the ISW layer is calculated from the mass and energy balance. This temperature-salinity relation is shown to depend only on the temperature and the salinity of the source water mass and to be practically independent of entrainment and melt rates. The model results are obtained without making any assumptions about entrainment and melt rates. The model is in good agreement with observations under the Ronne Ice Shelf, and it indicates that ISW in the Filchner Depression is formed from Western Shelf Water (WSW) with salinity higher than 34.75 practical salinity units. Such high-salinity water is only observed in the Ronne Depression in the western part of the continental shelf. This implies a circulation of WSW, under the Filchner-Ronne Ice Shelf, from the Ronne Depression into the Filchner Depression. Similarly, the model shows that the ISW observed under J9 at the Ross Ice Shelf has been formed from Low Salinity Shelf Water (LSSW) from the eastern parts of the Ross Sea continental shelf. LSSW must therefore circulate under the eastern parts of the Ross Ice Shelf.
Keywords: Antarktis; geofysikk; isshelf; kontinentalsokkel; oseanografi

The Crary Fan: A trough-mouth fan on the Weddell Sea continental margin, Antarctica - Kuvaas, Berit; Kristoffersen, Yngve (Marine Geology, 1991)
Multichannel seismic investigations show the presence of a large trough-mouth fan deposit on the continental margin in the southern Weddell Sea. A characteristic feature of the fan is relatively few, but large canyons and/or channels which appear to have been stable for long periods. Levees associated with the channels may reach thicknesses of more than 1 km. Drilling during ODP Leg 113 recorded the presence of glaciers in East Antarctica since early Oligocene time, and the seismic stratigraphic evidence suggests that the submarine fan is largely composed of glacigenic sediments. The channel-levee systems and complexes indicate several growth phases, apparently controlled by glacial/interglacial climate fluctuations, with maximum fan growth during glacial periods. The present interglacial period is characterized by strong and erosive flow of Ice Shelf Water running down the western slope of the fan and carrying only minor amounts of suspended matter. The fan is essentially sediment starved during interglacial periods. The dimensions of the channel-levee complexes and the persistent loci of sediment supply suggest that turbidite sedimentation resulted from melting of wet-based glaciers at or near the shelf edge, which has consequently prograded 70-80 km seaward.
Keywords: Sørishavet; Weddellhavet; havbunnen; isshelf; kontinentalmargin; kontinentalsokkel; marin geologi; seismologi

The tides of the southern Weddell Sea - Foldvik, Arne; Middleton, Jason H; Foster, Theodore D (Deep Sea Research Part A. Oceanographic Research Papers, 1990)
Keywords: Sørishavet; Weddellhavet; isshelf; kontinentalsokkel; kontinentalsokler; tidevann